(untitled) (Research, Society and Development, 2020)
The nursing professional performs essential actions in the hospital area, among them, the management of patient care in the perioperative period stands out, in which assistance actions focused on the comprehensive planning of the demands presented by them are highlighted. Thus, this study aimed to describe the experience of nursing students during the realization of a cycle of lectures on the role of nursing within this environment, with an emphasis on the quality of care provision. This is a study with a qualitative approach of the experience report type, based on the methodological basis of the Theory of Problematization of with the Arco de Maguerez, from which it became evident that some professionals did not put in practice the standardized criteria for the provision of a comprehensive perioperative patient care. Thus, action was taken to mitigate these situations. As the lectures took place, the scope and importance of the action was perceived, since the professionals actively participated in reporting their experiences and clearing up doubts, as well as punctuating aspects that reflected in the quality of care, such as work overload and exhaustion . In addition, they commented on the importance of actions aimed at promoting a more humanized and holistic view of the patient. Based on the above, it is concluded that the action developed served as a consolidating mechanism of the aspects that constitute the application of the principle of integrality, emphasizing the primary function of the nursing team in care management, as well as encouraging humanization and welcoming, as well as increasing the efficiency and quality of the services provided.